BIBLIOMETRIC ANALYSIS OF THE USE OF GIS TOOLS IN LANDSLIDE SCENERY ON BRAZIL - Pereira dos Santos, Arthur; Collins da Cunha e Silva, Darllan; Armando de Oro Arenas, Luis; Wagner Lourenço, Roberto (Revista Geográfica de América Central., 2025)
This research consists of a systematic review of articles that used Geographic Information Systems (GIS) as a way to map landslide-prone areas in Brazil or that experienced this situation. Data available for analysis in the Web Of Science and Scopus search collections were used, and the VOSViewer software was used. A methodology based on exclusion filters was applied, which allowed us to perceive a multidisciplinary approach to the theme and a concentration of published works in areas close to Serra do Mar. The results indicate a remarkable growth in this topic, with more than 60% of the papers published in the last 5 years and which were driven by the growth of research involving landslide predictions through Artificial Intelligence (AI) tools.